Esterification of glycerol with acetic acid over Lewatit catalyst - Setyaningsih Lucky; Siddiq Fahmi; Pramezy Aqila (MATEC Web of Conferences, 2018)
Tri Acetyl Glycerol or triacetin is one of the glycerol derivative products which can be used as additives in liquid fuels (octane boosters) to reduce knocking on the machine. The use of triacetin as octane booster is considered very promising because it comes from renewable and environmentally friendly raw materials. The resulting glycerol-based additives are suitable for gasoline, biodiesel and diesel. In this study glycerol esterification with acetic acid over Lewatit catalyst was investigated. The effects of various parameters, such as reaction temperature, weight of catalyst and molar ratio of glycerol to acetic acid were studied and the optimum condition for the triacetin synthesis are 100°C, 1: 7 mole of ratio and 3% weight of catalys